Analysis and Simulation of Airfoil with Joukowsky Transformation - Hutabarat, Eduward; Handayani, Vitri Aprilla (Journal of Science and Technology, 2020)
The equation of airfoil and its complex potential function can be produced from the Joukowsky transformation. The airfoil will call Joukowsky airfoil because it comes from the transformation. Using Wolfram Mathematica as a software simulator, this transformation produce airfoil with any variant graph and position, also mean camber line and position of trailing edge of airfoil. The complex potential function can also produce equation and graph of equipotential & streamlines.